Supplementary Figure S3 from Serologic Profiling Using an Epstein-Barr Virus Mammalian Expression Library Identifies EBNA1 IgA as a Prediagnostic Marker for Nasopharyngeal Carcinoma - Sarita Paudel (15047430) (2025)
Detection of EBV-specific IgM in sera from incident NPC cases and healthy controls in the SCHS cohort. Heatmap depicting IgM heavy chain-specific (IgMH) normalized detection values from 20 incident NPC case-control pairs and the data is represented similarly to Fig 2 with Fisher’s exact test identifying no protein that discriminated case from controls.